Guideline for sustainable wetland management and utilization: key cornerstones - Chuma, Edward; Masiyandima, Mutsa; Finlayson, C. Max; McCartney, Matthew P.; Jogo, W.; Motsi, Kudakwashe; Manzungu, Emmanuel; Chasi, Mutsa; Nenguke, Alleta; Sithole, Pinimidzai; Munguambe, Francisco; Hagmann, Juergen (2012)
This research report is based on the project on Wetlands, Livelihoods and Environmental Security and the Sustainable management of Inland Wetlands in Southern Africa: a livelihoods and ecosystem approach projects. The projects were supported by the CGIAR´s Challenge Programme on Water and Food (CPWF) and the Global Environment facility with matching funds from International Water Management Institute (IWMI), Eduardo Mondlane (UEM), FSP and the University of Zimbabwe (UZ) The authors acknowledge input by the entire project team. The support of IWMI, UEM, and the UZ, and Institute de Recherche pour le Development (IRD) during project implementation is gratefully acknowledged. The authors thank the input of CPWF Theme 3 leadership and the Limpopo Basin Coordinator during project implementation.